2021
DOI: 10.1186/s12882-021-02563-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for impaired renal function in HIV-infected and HIV-uninfected adults: cross-sectional study in North-Western Tanzania

Abstract: Background Although the burden of impaired renal function is rising in sub-Saharan Africa (SSA), little is known about correlates of impaired renal function in the region. We determined factors associated with estimated glomerular filtration rate (eGFR) and impaired renal function in HIV-infected and HIV-uninfected adults. Methods We undertook cross-sectional analysis of data from 1947 adults at enrolment for a cohort study on diabetes and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…In this study, age was a strong predictor of reduced eGFR, a finding similar to other studies in SSA [ 10 , 11 , 12 ]. Studies have shown that chronic HIV infection accelerates aging and, even among ALHIV well controlled on ART, there is still an increased risk of age-related renal function loss [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, age was a strong predictor of reduced eGFR, a finding similar to other studies in SSA [ 10 , 11 , 12 ]. Studies have shown that chronic HIV infection accelerates aging and, even among ALHIV well controlled on ART, there is still an increased risk of age-related renal function loss [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…eGFR was estimated from serum creatinine using the 2021 CKD-EPI equation and was used as a continuous outcome in the regression analysis. The 2021 CKD-EPI formula is a race-free formulae that has been widely used to assess renal insufficiency among Africans in SSA [ 11 , 12 ]. Use of race-based CKD-EPI has been shown to overestimate eGFR if applied among African populations, consequently resulting in delayed initiation of nephrological care including dialysis initiation [ 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia exacerbates the progression of HIV-associated nephrotoxicity, leading to structural and functional changes in the kidneys and promoting the development of CKD [114]. Furthermore, erythropoietin deficiency, a common feature in HIV-related anemia, not only contributes to inadequate red blood cell production but is also implicated in renal injury, creating a dual mechanism through which anemia may impact kidney health [115], as shown in Figure 4. Chronic inflammation and immune activation characteristic of HIV infection create a pro-inflammatory environment, directly affecting renal function and contributing to CKD.…”
Section: Chronic Anemia and Chronic Kidney Disease In Hivmentioning
confidence: 99%